Cytotoxicity of leaves, stems, and flowers of Kecubung (Datura metel) extracts using the Brine Shrimp Lethality Test (BSLT) method - Rindhira Humairani; Nanda Rizki Purnama; Herpandi Herpandi; Mochamad Syaifudin; Ilham Zulfahmi; Yusrizal Akmal; Muliari Muliari; Agus Putra AS; Agung Setia Batubara (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Brine shrimp (Artemia salina) cytotoxicity assays (BSLT) are one of the commonly used cytotoxic test methods to assess a plant extract's pharmacological activity and toxicity. Thus, this study aimed to examine the toxic levels of Kecubung (Datura metel) leaves extracted using different solvents, namely ethanol and ethyl acetate. The results showed that the LC50value of flower ethanol, flower ethyl acetate, leaf ethanol, and stem ethyl acetate extracts had an LC50value 1000, which was included in the toxic category. The LC50value of flower ethanol is 121.044 ppm, flower ethyl acetate 105.89 ppm, leaf ethanol 639.589 ppm, and stem ethyl acetate 635.276 ppm. Ethanol leaf extract at a concentration of 1000 ppm showed the highest mortality with a percentage of 60% of the total number ofA. salina. The flower ethanol extract showed the highest mortality at a concentration of 250 ppm with a percentage of 67% and at a concentration of 1000 ppm with a percentage of 70% of the total number ofA. salina. Meanwhile, flower ethyl acetate and stem ethyl acetate extract at a concentration of 1000 ppm obtained 100% mortality ofA. salinain the first 6 hours. The result shows that the flower ethyl acetate and stem ethyl acetate extract at a concentration of 1000 ppm is very toxic compared to other concentrations.Keywords:ToxicityArtemia salinaLC50Ethyl acetateEthanol